Spatial and temporal variability of environmental proxies from the top 120 m of two ice cores in Dronning Maud Land (East Antarctica) - Wauthy, Sarah; Tison, Jean-Louis; Inoue, Mana; El Amri, Saïda; Sun, Sainan; Fripiat, François; Claeys, Philippe; Pattyn, Frank (Earth System Science Data, 2024)
The Antarctic ice sheet's future contribution to sea level rise is difficult to predict, mostly because of the uncertainty and variability of the surface mass balance (SMB). Ice cores are used to locally (kilometer scale) reconstruct SMB with a very good temporal resolution (up to sub-annual), especially in coastal areas where accumulation rates are high. The number of ice core records has been increasing in recent years, revealing an important spatial variability and different trends of SMB, highlighting the crucial need for greater spatial and temporal representativeness. We present records of density, water stable isotopes (δ18O, δD, and deuterium excess), major ions concentrations (Na+, K+, Mg2+, Ca2+, MSA, Cl−, SO42-, and NO3-), and continuous electrical conductivity measurement (ECM), as well as age models and resulting surface mass balance from the top 120 m of two ice cores (FK17 and TIR18) drilled on two adjacent ice rises located in coastal Dronning Maud Land and dating back to the end of the 18th century. Both environmental proxies and SMB show contrasting behaviors, suggesting strong spatial and temporal variability at the regional scale. In terms of precipitation proxies, both ice cores show a long-term decrease in deuterium excess (d-excess) and a long-term increase in δ18O, although less pronounced. In terms of chemical proxies, the non-sea-salt sulfate ( nssSO42-) concentrations of FK17 are twice those of TIR18 and display an increasing trend on the long-term, whereas there is only a small increase after 1950 in TIR18. The SO42-/Na+ ratios show a similar contrast between FK17 and TIR18 and are consistently higher than the seawater ratio, indicating a dominant impact of the nssSO42- on the SO42- signature. The mean long-term SMB is similar for FK17 and TIR18 (0.57 ± 0.05 and 0.56 ± 0.05 mi.e.yr-1, respectively), but the annual records are very different: since the 1950s, TIR18 shows a continuous decrease while FK17 has shown an increasing trend until 1995 followed by a recent decrease. The ...